(untitled) (Research Journal of Padmakanya Multiple Campus, 2025)
This study investigates the relationship between career development and employee commitment in Nepalese commercial banks, with a focus on the moderating role of gender. Career development, including career planning, professional development, compensation and benefits, job security, and growth opportunities, plays a critical role in enhancing employee commitment as an essential factor for organizational success and talent retention. Using a quantitative research design and data collected from 381 employees across three different types of commercial banks in Nepal, the study employs moderation analyses to test the impact of gender on the relationship between career development and employee commitment. Findings indicate that career development positively and significantly predicts employee commitment across genders, with career planning and professional development showing stronger effects for one gender group. Job security and growth opportunities emerge as the most influential predictors overall, while compensation and benefits show a weaker association when accounting for other factors. The study contributes to the literature by highlighting gender-specific factors, emphasizing the importance of gender-responsive human resource strategies in Nepalese banking institutions to boost equitable and sustained employee commitment.